2015
DOI: 10.1099/ijs.0.000074
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomonas gei sp. nov., isolated from roots of Geum aleppicum

Abstract: A yellow-pigmented bacterium, designated strain ZFGT-11 T , was isolated from roots of Geum aleppicum Jacq. collected from Taibai Mountain in Shaanxi Province, north-west China, and was subjected to a taxonomic study by using a polyphasic approach. Cells of strain ZFGT-11 T were Gram-stain-negative, strictly aerobic rods that were surrounded by a thick capsule and were motile by means of a single polar flagellum. Phylogenetic analyses based on 16S rRNA gene sequences showed that strain ZFGT-11 T was a member o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…16S rRNA gene amplicon sequencing revealed that Sphingomonas was the most frequently detected genus in the air samples. This genus has been found in various environments such as soil, water, clinical specimens, air, and other locations [30][31][32], indicating the opportunity for the bacteria to be released into the air. Pseudomonas and Achromobacter were signi cantly more abundant in air samples from bathrooms and other indoor sites, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…16S rRNA gene amplicon sequencing revealed that Sphingomonas was the most frequently detected genus in the air samples. This genus has been found in various environments such as soil, water, clinical specimens, air, and other locations [30][31][32], indicating the opportunity for the bacteria to be released into the air. Pseudomonas and Achromobacter were signi cantly more abundant in air samples from bathrooms and other indoor sites, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…S4). The pH range for growth was determined in R2A medium at pH 4.0-10.0 at intervals of 1 pH unit by using the buffers 0.1 M citric acid/0.1 M sodium citrate (pH 4.0-5.0), 0.2 M Na 2 HPO 4 /0.2 M NaH 2 PO 4 (pH 6.0-8.0) and 0.1 M NaHCO 3 /0.1 M Na 2 CO 3 (pH 9.0-10.0) [34]. Growth on different media [nutrient agar, tryptic soy agar (15 g casein peptone, 5 g soy peptone, 5 g sodium chloride, 15 g agar per litre of laboratory quality water, pH 7), PTYG agar (0.25 g peptone, 0.25 g tryptone, 0.5 g yeast extract, 0.5 g glucose, 0.6 g MgSO 4 ·7H 2 O, 70 mg CaCl 2 ·2H 2 O and 15 g agar per litre of laboratory quality water, pH 7), PY agar (10 g peptone, 2 g yeast extract, 1 g MgSO 4 ·7H 2 O and 15 g agar per litre of laboratory quality water, pH 7)] was assessed on agar plates under 15 °C.…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%
“…These data suggest that the strongly labeled cellulolytic strain is degrading 13 C-cellulose extracellularly and the weakly 13 C-enriched strain can access degradation products as well as other sources of unlabeled carbon present in soil. The capacity of Sphingomonas species to degrade cellulose through the activity of extracellular enzymes is known [65,66].…”
Section: Mutualists Opportunists and Parasitesmentioning
confidence: 99%